Motivational influences on computer-related affective states. - Coffin, R. J.; MacIntyre, P. D. (Computers in Human Behavior, 1999)
A study was conducted to analyze the effects of motivation to learn to use computers and previous experience with computers on three computer-related affective states—anxiety, attitudes, and self-efficacy. Subjects were 59 male and 52 female university and college students enrolled in introductory computer programming and fundamental courses. Findings revealed gender differences in prior experience with computers, as well as in most of the motivation and all of the affective variables. Results of a path analysis used to further examine these relations and to explore their impact on academic performance in introductory computer classes supported the theoretical model, with some modifications, Gender differences in structure were found to be negligible. When students were grouped according to reasons for taking the course—intrinsic, extrinsic, or both—significant differences among the three groups were observed for six of the ten variables examined, in all cases favoring an intrinsic motivational orientation.